2022
DOI: 10.1101/2022.02.09.478817
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The isoforms of pyruvate kinase act as nutrient sensors for the β-cell KATP channel

Abstract: As nutrient sensors for the organism, pancreatic β-cells use metabolism as a signaling pathway to elicit insulin secretion. Phosphoenolpyruvate (PEP), the substrate for pyruvate kinase (PK), may be a critical signaling intermediate based on its ability to locally control ATP-sensitive K+ (KATP) channels on the plasma membrane. Using isoform-specific deletion, we show that constitutively-active PKm1 is sufficient for KATP closure. Yet, it is the minor but allosterically-tunable PKm2 isoform that enables glucose… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…RNA-Seq of islets from β-Zfp148 KO and control mice identified numerous genes that control nutrient responses. We demonstrated that 1 or more of these pathways converge to enhance PEP cycling and, consequently, pyruvate kinase-derived ATP production (Figures 2 and 5, and Supplemental Figures 2 and 3), the direct activator of K ATP channel closure and a known regulator of insulin secretion (22,37).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…RNA-Seq of islets from β-Zfp148 KO and control mice identified numerous genes that control nutrient responses. We demonstrated that 1 or more of these pathways converge to enhance PEP cycling and, consequently, pyruvate kinase-derived ATP production (Figures 2 and 5, and Supplemental Figures 2 and 3), the direct activator of K ATP channel closure and a known regulator of insulin secretion (22,37).…”
Section: Discussionmentioning
confidence: 89%
“…Glutamate dehydrogenase (GDH) plays a key role in amino acid-induced stimulation of insulin secretion (36). β Cells express high levels of mitochondrial phosphoenolpyruvate carboxykinase (Pck2), and deletion of this gene dramatically reduces insulin secretion and blocks amino acid-stimulated Ca 2+ influx at low glucose levels (23,37). Activators of pyruvate kinases stimulate insulin secretion (22).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations